MODEL PERENCANAAN DAN PENGELOLAAN LINGKUNGAN BERBASIS MASYARAKAT KASUS : BENTANGLAHAN KAWASAN TEMBALANG SEMARANG - Samadikun, Budi Prasetyo; Sudibyakto, Sudibyakto; Setiawan, Bakti; Rijanta, Rijanta (Universitas Diponegoro, 2012)
One of mayor requirement in environmental system planning and management is to predict the condition in the future. Model can be used to simplified the prediction and arrangement of anything. There are four steps as a guidance for making a model, i.e.: model formulation, parameter identification, parameter estimation, and model validation. The result being expected after applying those four steps is a good model that consistent with study objective, simple, and applicable.